Mężczyzna w edukacji przedszkolnej: prolegomena do badań w Polsce/ Male in the occupation of a nursery school teacher: prolegomena to empirical research in Poland - Urszula Ordon (Language, Culture, Politics)
The author’s objective is to investigate the principal directions of research into the presence and the role of a male in nursery school education in Poland and in the world. Hence, the subject-matter of this research is concentrated upon the following questions: • what is the state of research into the factors determining the participation of males in nursery school education in Poland, and also in the world? • what are the crucial issues included into the direction of research described herein? • what are the recommendations relevant to the practice of nursery school education within the scope of employing males in the capacity of teachers? In the research, the analytic-synthetic method of investigating the literature of the subject is applied. The paper is commenced with the analysis of the state of research in Poland. The state in question is set against the one of research conducted in other countries. The principal directions of research into the issue of employing males in nursery school education, highlighting both their achievements and shortcomings alike, are shed light upon. The analysis of the state of research in Poland leads to a conclusion that the representatives of Polish pedagogical sciences into the issue of the presence or the absence of males in nursery school education whereas research abroad is well advanced. This includes a broad scope of issues, from the problem of equality in the labor market, the social perception of male nursery school teachers to their strategies of action, and fulfilling male roles in the feminized working environment, collaboration with females and the latter's perception of their male colleagues at work, to research into the perception of nursery school teachers by children and their influence upon the development of children. The fact that the issue of the role of males in early child education is not a subject-matter of Polish research seems to be a major gap, which ought to be filled in without delay. The presented article aims at rendering it easier for possible researchers to investigate key issues, which have already been analyzed abroad for three decades. Reflecting upon theory ought to be accompanied by educational and social programs making general public aware of the necessity of males’ involvement in the process of child's education, and also employing them in a larger number in the institutions of nursery school education.